Kepemimpinan Perempuan: Penerapan Metode Tafsir Hermeneutika Feminisme Amina Wadud - Arsal Arsal; Busyro Busyro; Maizul Imran (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Women's Leadership: The Application of the Feminist Hermeneutic Interpretation Method of Amina WadudRevealing and also criticizing Amina Wadud's interpretation of feminist hermeneutics in the context of women's leadership in the public field of modern era is the aim of this article. To understanding God's messages contained in His words is certainly not easy and requires a special method that is popularly referred to as takwil and tafsir. On the other hand, the dynamics of human culture development are constantly evolving and almost unstoppable which will indirectly also affect the interpretation of the Qur'an. Many various methods of interpretation were introduced by scholars to explore their contents from classical methods to modern methods. Among the emerging modern methods is the hermeneutics feminism which was pioneered by Amina Wadud. According to him the classical interpretation model is no longer relevant to the modern context, especially in terms of addressing gender. Nearly the results of the classical interpretation are gender deviations and take side to male. Therefore, the interpretation of the Qur'an is expectedly just, and then the interpretation model should be adjusted to the modern context rather than looking at the past, especially with regard to the position of women. This paper will highlight this event using a socio-historical approach and content analysis. In addition, references related to the patterns of Islam integrity and culture will be used with a comparative pattern. The conclusion of this research is that Wadud based his interpretation method on the language, justice, and equality aspects. According to him,a woman can be a leader both in the domestic and public today. Wadud set his opinion based on the textual meaning consideration of the verse without considering the hadith explanation